Egr2-guided histone H2B monoubiquitination is required for peripheral nervous system myelination - Wüst, Hannah; Wegener, Amelie; Fröb, Franziska; Hartwig, Anna; Wegwitz, Florian; Kari, Vijayalakshmi; Schimmel, Margit; Tamm, Ernst R.; Johnsen, Steven A.; Wegner, Michael; Sock, Elisabeth (Nucleic Acids Research, 2020)
Schwann cells are the nerve ensheathing cells of the peripheral nervous system. Absence, loss and malfunction of Schwann cells or their myelin sheaths lead to peripheral neuropathies such as Charcot-Marie-Tooth disease in humans. During Schwann cell development and myelination chromatin is dramatically modified. However, impact and functional relevance of these modifications are poorly understood. Here, we analyzed histone H2B monoubiquitination as one such chromatin modification by conditionally deleting the Rnf40 subunit of the responsible E3 ligase in mice. Rnf40-deficient Schwann cells were arrested immediately before myelination or generated abnormally thin, unstable myelin, resulting in a peripheral neuropathy characterized by hypomyelination and progressive axonal degeneration. By combining sequencing techniques with functional studies we show that H2B monoubiquitination does not influence global gene expression patterns, but instead ensures selective high expression of myelin and lipid biosynthesis genes and proper repression of immaturity genes. This requires the specific recruitment of the Rnf40-containing E3 ligase by Egr2, the central transcriptional regulator of peripheral myelination, to its target genes. Our study identifies histone ubiquitination as essential for Schwann cell myelination and unravels new disease-relevant links between chromatin modifications and transcription factors in the underlying regulatory network.
CRIS-Team Scopus Importer:2020-10-02